Antireflux versus conventional self-expanding metallic Stents (SEMS) for distal esophageal cancer: results of a multicenter randomized trial - Coron, E.; David, G.; Lecleire, S.; Jacques, J.; Le Sidaner, A.; Barrioz, T.; Coumaros, D.; Volteau, C.; Vedrenne, B.; Bichard, P.; Boustière, C.; Touchefeu, Y.; Brégeon, J.; Prat, F.; Le Rhun, M.; and the Société Française d’Endoscopie Digestive (SFED) (Endoscopy International Open, 2016)
Introduction: Self-expanding metal stents (SEMS) are commonly used in the palliation of dysphagia in patients with inoperable esophageal carcinoma. However, they predispose to gastroesophageal reflux when deployed across the gastroesophageal junction. The aims of this study were to: 1) assess the influence of the antireflux valve on trans-prosthetic reflux (primary outcome); and 2) compare the results of SEMS with and without antireflux valve in terms of reflux symptoms, quality of life (QOL), improvement of dysphagia and adverse events (secondary outcomes).Patients and methods: Thirty-eight patients were enrolled in nine centers. Carcinomas were locally advanced (47 %) or metastatic. After randomization, patients received either a covered SEMS with antireflux valve (n = 20) or a similar type of SEMS with no antireflux device but assigned to standard proton pump inhibitor therapy and postural advice (n = 18). Trans-prosthetic reflux was assessed at day 2 using a radiological score based on barium esophagography performed after Trendelenburg maneuver and graded from 0 (no reflux) to 12 (maximum). Monthly telephone interviews were conducted for Organisation Mondiale de la Santé (OMS) scoring from 0 (excellent) to 5 (poor), QOL assessment (based on the Reflux-Qual Simplifié scoring system) from 0 (poor) to 100 (excellent), dysphagia scoring from 0 (no dysphagia) to 5 (complete dysphagia) and regurgitation scoring from 0 (no regurgitation) to 16 (maximum).Results: No difference was noted in terms of age, sex, size of lesion, prosthesis length or need for dilation prior to SEMS placement. No difficulty in placing SEMS nor complications were noted. Radiological scores of reflux were found to be significantly lower in patients with an antireflux stent compared to the conventional stent and associated measures. The regurgitation scores were significantly decreased in patients with antireflux stents during the first 2 months after stent placement and thereafter, they were similar in the two groups. QOL and dysphagia were improved in both groups. Survival rates were comparable in the two groups.Conclusions: No difference was observed between the two types of SEMS regarding the palliation of dysphagia and improvement of QOL. However, SEMS with an antireflux valve were more effective in preventing trans-prosthetic gastroesophageal reflux but at the cost of an increased likehood of minor adverse events (migrations and/or obstruction of the SEMS).